2010
DOI: 10.1063/1.3274663
|View full text |Cite
|
Sign up to set email alerts
|

Short-time dynamics of permeable particles in concentrated suspensions

Abstract: First-order virial expansion of short-time diffusion and sedimentation coefficients of permeable particles suspensions Phys. Fluids 23, 083303 (2011); 10.1063/1.3626196 Rotational and translational self-diffusion in concentrated suspensions of permeable particles We present a comprehensive computational study of the short-time transport properties of bidisperse hard-sphere colloidal suspensions and the corresponding porous media. Our study covers bidisperse particle size ratios up to 4 and total volume fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
95
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(108 citation statements)
references
References 69 publications
12
95
1
Order By: Relevance
“…It has been checked that for a wide range of particle internal structures and boundaries, and the no-overlap direct interactions, deviations from the above approximation are very small [29,31,32,34] and as such, hard to be detected in experiments, even for relatively dense suspensions.…”
Section: Discussionmentioning
confidence: 99%
“…It has been checked that for a wide range of particle internal structures and boundaries, and the no-overlap direct interactions, deviations from the above approximation are very small [29,31,32,34] and as such, hard to be detected in experiments, even for relatively dense suspensions.…”
Section: Discussionmentioning
confidence: 99%
“…7. For monodisperse suspensions, U s /U 0 from Ladd 81 and Abade et al 91 are also shown in Fig. 7(a) for comparison.…”
Section: Instantaneous Sedimentation Velocitymentioning
confidence: 99%
“…We have calculated to high precision both k H (from the series expansion of J(r) in inverse powers of r) and η ∞ (using a hydrodynamic multipole method corrected for lubrication [39][40][41][42], encoded in our hydromultipole program package extended to porous spheres [43,44]). The hydrodynamic structure of the particles enters into the hydromultipole code through a single-particle friction operator only, whose form is known for a variety of particle models with different internal hydrodynamic structures [39,52].…”
Section: Resultsmentioning
confidence: 99%
“…The many-sphere hydrodynamic interactions in a concentrated system of porous spheres are fully accounted for by our precise hydrodynamic multipole method (see [39][40][41][42] for details) encoded in the hydromultipole program which we have extended by the inclusion of particle porosity [43,44]. Using this method, we have obtained data for η ∞ for volume fractions φ covering the equilibrium fluid phase regime.…”
Section: Introductionmentioning
confidence: 99%